Prevalence & correlates of chronic perinatal pain - a study from India - Geetha Desai; G. Sunil Kumar; L. Manoj; G. R. Gokul; K. V. Beena; K. Thennarasu; T. S. Jaisoorya (Taylor & Francis Group, 2019)
Objectives: To study the prevalence of chronic perinatal pain among mothers who had infants between the ages of 13-25 months in the State of Kerala, India and to report its correlates in the socio-demographic, obstetric and psychological domains. Methods: A total of 9305 mothers selected by cluster random sampling were assessed cross-sectionally for chronic perinatal pain using a questionnaire by Junior Public Health Nurses (JPHNs). In addition, information regarding socio-demographic profile, obstetric history, infant details and perinatal depression were collected. Results: Of the 8302 (89.3%) valid responses, 552 (6.6%) mothers reported chronic perinatal pain. Among those with pain, 142 (25.6%) reported pain during pregnancy, 314 (56.7%) during postpartum and 96 (17.7%) during both periods. The commonest sites of pain reported were back 280 (51%) and pelvic region 110 (19%). Mothers with chronic perinatal pain were more likely to be younger, less educated, employed and from an urban background. Chronic perinatal pain was associated with obstetric complications, delivery by instrumental/caesarean section, non-exclusive breast feeding and higher maternal depression scores. Conclusion: Chronic pain is common among mothers in India during the perinatal period and greater attention needs to be given for it to be recognised and treated early.